Speeding the Detection of Vessel Cannulation: An In-Vitro Stimulation Study - Muffly, Matthew K.; Ku, Andrew; Drover, David R.; Rodriguez, Samuel; Caruso, Thomas J.; Ku, Anne; Tsui, Ban C. H. (Anesthesia and analgesia, 2020)
BACKGROUND:Some practitioners “prime” small IV angiocatheter needles with 0.9% sodium chloride—claiming this modification speeds visual detection of blood in the angiocatheter flash chamber on vessel cannulation. METHODS:We compared the time required for human blood to travel the length of saline-primed and saline-unprimed 24- and 22-gauge angiocatheter needles (Introcan Safety IV Catheter; B. Braun, Bethlehem, PA). A syringe pump (Medfusion 4000, Cary, NC) advanced each angiocatheter needle through the silicone membrane of an IV tubing “t-piece” (Microbore Extension Set, 5 Inch; Hospira, Lake Forest, IL) filled with freshly donated human blood. When the angiocatheter needle contacted the blood, an electrical circuit was completed, illuminating a light-emitting diode. We determined the time from light-emitting diode illumination to visual detection of blood in the flash chamber by video review. We tested 105 saline-primed angiocatheters and 105 unprimed angiocatheters in the 24- and 22-gauge angiocatheter sizes (420 catheters total). We analyzed the median time to visualize the flash using the nonparametric Wilcoxon rank sum test in R (http://www.R-project.org/). The Stanford University Administrative Panel on Human Subjects in Medical Research determined that this project did not meet the definition of human subjects research and did not require institutional review board oversight. RESULTS:In the 24-gauge angiocatheter group, the median (and interquartile range) time for blood to travel the length of the unprimed angiocatheter needle was 1.14 (0.61–1.47) seconds compared with 0.76 (0.41–1.20) seconds in the saline-primed group (P = 0.006). In the 22-gauge catheter group, the median (interquartile range) time for blood to travel the length of the unprimed angiocatheter needle was 1.80 (1.23–2.95) seconds compared with 1.46 (1.03–2.54) seconds in the saline-primed group (P = .046). CONCLUSIONS:These results support the notion that priming small angiocatheter needles, in particular 24-gauge catheters, with 0.9% sodium chloride may provide earlier detection of vessel cannulation than with the unprimed angiocatheter.